Beban Kerja Mental Perawat Ruang Kritis dan IGD di RSUD Kota Bandung - Tia Dwi Aprilia; Irman Somantri; Ristina Mirwanti (Journal of Nursing Care, 2019)
Nurses who work in intensive care unit and emergency rooms have excessive workload, and they are required to carry out nursing interventions appropriately and quickly. The heavy workload has an impact on the nurse's mentality, however limited information about the nurse's mentality related to workload. The aim of the study was to identify the mental workload of nurses in intensive care and emergency rooms. Method, this research is quantitative descriptive study with total sampling technique, 63 nurses who worked in ICU, PICU / NICU, and IGD of RSUD Kota Bandung involved in this study. The research instrument was NASA-TLX (National Aeronautics and Space Administration-Task Load Index). Data were analyed using descriptive analysis in the form of frequency distribution and mean. The results showed that nurses in the emergency room (42.9%) had high mental workload, and the moderate mental workload identified in nurses who works the PICU / NICU and ICU rooms. Conclusion, critical care rooms and emergency room should consider nurses’ working balance and fulfill their rest needs. Further research is needed to examine the efforts that can be made to reduce nurses' mental workload.